2011
DOI: 10.1007/s12078-011-9094-4
|View full text |Cite
|
Sign up to set email alerts
|

Use of an Immediate Swallow Protocol to Assess Taste and Aroma Integration in fMRI Studies

Abstract: Perception of flavor is a complex process involving the integration of taste and aroma. Few functional magnetic resonance imaging (fMRI) studies have assessed the crossmodal interactions which result in flavor perception, and all previous studies have used a retro-nasal aroma delivery with a delayed swallow, which delays retro-nasal aroma release, and thus, alters taste and aroma integration. In this paper, we assess crossmodal interactions in flavor processing using an immediate swallow fMRI paradigm in 13 he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 25 publications
(79 reference statements)
1
9
0
Order By: Relevance
“…f MRI provides a great tool to understand the cortical association and integration between the different modalities. Evidence from recent f MRI studies show overlapping brain responses to taste and aroma in areas including anterior insula, ACC, OFC and amygdala (43)(44)(45)(46)(47) . Verhagen and Engelen performed a meta-analysis, which suggested the anterior insula to be a multi-modal area activated by both taste and aroma stimuli (48) .…”
Section: Functional Mri Responses To Taste Aroma and Oral Somatosensmentioning
confidence: 99%
“…f MRI provides a great tool to understand the cortical association and integration between the different modalities. Evidence from recent f MRI studies show overlapping brain responses to taste and aroma in areas including anterior insula, ACC, OFC and amygdala (43)(44)(45)(46)(47) . Verhagen and Engelen performed a meta-analysis, which suggested the anterior insula to be a multi-modal area activated by both taste and aroma stimuli (48) .…”
Section: Functional Mri Responses To Taste Aroma and Oral Somatosensmentioning
confidence: 99%
“…Five studies reported the body mass index (BMI; mean ± SD) of their participants (Haase et al., , 23.7 without SD; Eldeghaidy et al., , 24 ± 4; Green & Murphy, , 25.0 ± 5.6; Green et al., , 24 ± 2.7; Avery et al., , 29 ± 6). All reported mean BMI values were below 30, the cut‐off threshold of obesity as defined by World Health Organization (World Health Organization, ).…”
Section: Resultsmentioning
confidence: 99%
“…One AFNI study (Green & Murphy, 2012) involved the use of FMRIB Software Library (FSL, another software program). Participants in 13 studies needed to swallow the taste sample liquids (Avery et al, 2015;Bender, Veldhuizen, Meltzer, Gitelman, & Small, 2009;Cerf-Ducastel, Haase, & Murphy, 2012;Eldeghaidy et al, 2011;Green, Jacobson, Haase, & Murphy, 2013;Green & Murphy, 2012;Haase, Cerf-Ducastel, Buracas, & Murphy, 2007;Haase, Cerf-Ducastel, & Murphy, 2009;McCabe & Rolls, 2007; O'Doherty, Rolls, Francis, Bowtell, & McGlone, 2001;Small et al, 2003;Veldhuizen, Bender, Constable, & Small, 2007;Veldhuizen, Nachtigal, Teulings, Gitelman, & Small, 2010), while those in the remaining three studies did not (Kami et al, 2008;Nakamura et al, 2011Nakamura et al, , 2012.…”
Section: Study and Participant Profilesmentioning
confidence: 99%
See 1 more Smart Citation
“…Small [] proposed that the oral SSC participates in the process of oral referral and the binding of multimodal inputs into a flavor percept (cf. Eldeghaidy et al, []). Our findings extend these views to the processing of oral fat texture.…”
Section: Discussionmentioning
confidence: 99%